Stem cell-derived neuronal relay strategies and functional electrical stimulation for treatment of spinal cord injury. (December 2021) - Lai, Bi-Qin; Zeng, Xiang; Han, Wei-Tao; Che, Ming-Tian; Ding, Ying; Li, Ge; Zeng, Yuan-Shan
Abstract: The inability of adult mammals to recover function lost after severe spinal cord injury (SCI) has been known for millennia and is mainly attributed to a failure of brain-derived nerve fiber regeneration across the lesion. Potential approaches to re-establishing locomotor function rely on neuronal relays to reconnect the segregated neural networks of the spinal cord. Intense research over the past 30 years has focused on endogenous and exogenous neuronal relays, but progress has been slow and the results often controversial. Treatments with stem cell-derived neuronal relays alone or together with functional electrical stimulation offer the possibility of improved repair of neuronal networks. In this review, we focus on approaches to recovery of motor function in paralyzed patients after severe SCI based on novel therapies such as implantation of stem cell-derived neuronal relays and functional electrical stimulation. Recent research progress offers hope that SCI patients will one day be able to recover motor function and sensory perception.